A new species of Thaumastocoris Kirkaldy from Argentina (Heteroptera: Thaumastocoridae: Thaumastocorinae) - Carpintero, Diego Leonardo; Dellapé, Pablo Matías (Zootaxa, 2006)
Thaumastocoris peregrinus n. sp. from Argentina is described. New morphological characters are studied and compared with other related species. This is the first record of a member of the subfamily Thaumastocorinae (Thaumastocoridae) from the New World.